Evaluación del proceso de obtención de polisacáridos tipo glucano presentes en la ganoderma lucidum a nivel laboratorio para Nutrisetas S.A.S (2016)
In this paper the process of obtaining the type polysaccharides glucan present in the Ganoderma lucidum, for which four extraction processes such as Soxhlet extraction. Extraction with hot water, cold water and alkaline extraction were performed by varymg the extraction conditions were evaluated as solvents, time and temperature. The extracts obtained were characterized by DNS test with which it was possible lo identify reducing sugars. Atomic force microscope to Identify chains lentinan and Infrared Spectroscopy to identify the types of links.